Effectiveness of industrial rubber as roller material for rice processing machine - Adisa, Alex Folami; Mamah, Kevin Chinweike; Aderinlewo, Adewole Ayobami; Ismaila, Salami Olasunkanmi (Agriculture and Natural Resources, 2020)
The purpose of this study was to evaluate the performance and effectiveness of a developed roller rice dehusking and destoning machine at the Department of Agricultural and Bioresources Engineering, Federal University of Agriculture, Abeokuta, Nigeria by using an industrial rubber as roller material to replace Teflon rollers. This study modified and evaluated the performance of the dehusking and destoning machine on four varieties of paddy: NERICA L-42, NERICA 2, FARO 55 and OFADA, dried at five different ranges of moisture content (wet basis): A (11.00–12.99%), B (13.00–14.99%), C (15.00–16.99%), D (17.00–18.99%) and E (19.00–20.99%). Analysis of variance of the two main factors for the four paddy varieties was used to obtain the optimum machine operational parameters. The optimum values obtained for the coefficient of dehulling (Eh), coefficient of wholeness (ew), dehulling efficiency (eh) and cleaning efficiency (CE) were 0.77, 0.88, 65.65% and 97%, respectively, which were better than for the Teflon rollers. The effects of moisture content on Eh, ew, and eh were significant (p < 0.05).